Prevalence and characterization of Vero cytotoxin-producing Escherichia coli isolated from diarrhoeic and healthy sheep and goats. - Orden, J. A. (Cambridge University Press, 2003)
Faecal samples from 146 diarrhoeic lambs and goat kids, and from 511 healthy sheep and goats were screened for the presence of Vero cytotoxin-producing Escherichia coli (VTEC). In healthy sheep and goats, VTEC were isolated in 24.4 and 16.2% of the animals, respectively. Moreover, VTEC were detected in 3.1 and 5.9% of the diarrhoeic lambs and goat kids, respectively. These data suggest that VTEC seems not to be associated with diarrhoea in lambs and goat kids. Only four VTEC strains were eae-positive. The absence of the eae gene in most of these VTEC strains could indicate that these strains are less virulent for humans that the classical eae-positive enterohaemorrhagic E. coli types. However, almost half (42.9%) and 12.2% of VTEC strains isolated from healthy sheep and goats, respectively, belonged to serotypes associated with severe diseases in humans.